ESG (Environment, Social, Governance) and Tourism collaboration to Maximize Potential in Implementing the Blue Economy in the Banyuwangi Region - Fathur Rosi; Arianto, Bisma (SEAN Institute, 2024)
Blue economy is a collection of activities that maximize maritime potential and are coupled with economic activities. The blue economy studied in this paper is related to tourism and the management activities of fishermen's catches. By maximizing regional, social, government, and tourism potential, researchers discovered the fact that the blue economy in the Banyuwangi Regency area will be formed strongly. In the ESG concept, researchers have determined that all three components have been fulfilled, both in terms of environment, social, and governance. These three concepts will be developed together with tourism to strengthen the blue economy concept in the Banyuwangi Regency area. The development of this concept will be prolonged because maximizing the blue economy cannot be measured and implemented in less than five years.